EFEKTIVITAS MANAJEMEN PROGRAM PEMBELAJARAN BAHASA INGGRIS DI SMP NEGERI SAMARINDA - Idrus Idrus (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2014)
This study is aimed at obtaining a clear picture on the English teaching learning program management of state senior high schools in Samarinda,  observed from the managerial functions of planning, organizing, actuating, and controlling. The study used survey design. The subject of the study was the whole state senior hogh schools in Samarinda. To collect tye data, the researcher used questionnaire. Data were analyzed using descriptive statistics, in terms of rate percentage and tabulation. The result of the descriptive data analyses shows that the average of the effectiveness of the English learning program management of state senior high schools in Samarinda goes into average level.